You are fatally invited : a novel - Pliego, Ande (Bantam, 2025)
"When renowned anonymous author J. R. Alastor hires former aspiring writer Mila del Anǧl to host a writing retreat at his private manor off the coast of Maine, she jumps at the chance--particularly since she has an axe to grind with one of the invitees. The guest list? Six thriller authors, all masters of deceit, misdirection, and mayhem. Alastor and Mila have masterminded a week of games, trope-fueled riddles, and maybe a jump scare or two--the perfect cover for Mila to plot a murder of her own. But when a guest turns up dead--and it's not the murder she planned--Mila finds herself trapped in a different narrative altogether. With a storm isolating the island, and the body count rising, Mila must outwit a killer who knows literally every trick in the book"--